Comparison of the Use of Linear Quadratic Regulator and Linear Quadratic Tracker Optimal Control Techniques in DC Motor Systems with Noise Addition for the Development of Sustainable Technology Solutions in Community Empowerment - Gianni Masyitah Dwi Arimbi Puteri Yassin (Politeknik Perkapalan Negeri Surabaya, 2024)
DC motors are widely used in various sectors, including industrial applications, household appliances, and even children's toys. This research presents a system identification process for a DC motor using experimental techniques with the system identification tool in Matlab. The study explores optimal control techniques, specifically Linear Quadratic Regulator (LQR) and Linear Quadratic Tracker (LQT), to analyze the step response of the system. Understanding the transfer function of the DC motor is crucial for effective control; this is achieved by adjusting the Q and R matrices in the LQR technique, which ultimately modifies the value of the feedback gain, K. The Linear Quadratic Tracking (LQT) system aims to adjust the output to follow a predetermined trajectory, offering a dynamic tracking solution. To apply these control techniques, the DC motor is first modeled in the Laplace domain of order 2 and then transformed into the state-space domain, allowing for integration into LQR and LQT calculations. In this study, noise is introduced to assess the system's performance under both normal and noisy conditions, highlighting the resilience of the control methods. The control process, including the simulation and implementation of LQR and LQT calculations, is conducted using Simulink in Matlab. This research is of particular relevance to community empowerment initiatives, where the principles of optimal control can be applied to improve local technological solutions. The application of these control techniques to affordable, low-cost DC motor systems can significantly contribute to the development of sustainable technology in underprivileged communities, enhancing the accessibility and efficiency of small-scale industrial solutions. The findings aim to support practical applications in fields such as renewable energy, agricultural machinery, and local craftsmanship, offering a pathway to economic growth through technology.